PEMBINAAN EKONOMI KREATIF PADA SISWA SISWI SMK DI BATAM - L. Tobing, Vargo Christian; Purba, Tiurniari; Nainggolan, Nora Pitri; Natalia, Erni Yanti (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
The creative economy is a concept in the new economic era that intensifies information and creativity by relying on ideas and knowledge from human resources as the main production factors. This concept is usually supported by the existence of the creative industry which is its embodiment. Over time, economic development has reached the level of the previous creative economy, the world is faced with the concept of an information economy where information becomes the main thing in economic development. Considering the great benefits of the creative economy industry for economic growth, it is good to introduce the creative economy industry to the younger generation from an early age. Objective: To carry out community service coaching for school targets on the creative industry with the participants being vocational high school students in Batam. This community service is carried out by introducing the creative economy industry, its benefits and prospects for economic growth. Method: This community service is carried out using lecture and discussion methods. Results: By carrying out creative economy coaching, students can have an interest in contributing to the creative economy. Conclusion: During the community service activities, the participants were very enthusiastic about the material and discussions provided.